Correction to: Impact of Regulation (EU) No. 536/2014 on clinical trial approval processes in two Italian oncology centers - Daniela Bencardino; Fabiana Marchetti; Cristina Mazzi; Marianna Ferrari; Francesca Garibaldi; Giulia Ferrera; Giulia Ponti; Chiara Altavilla; Laura Rossi; Matteo Verzè; Vanda Salutari; Vincenzina Mora; et al. (Journal of Pharmaceutical Innovation, 2026)

Impact of Regulation (EU) No. 536/2014 on clinical trial approval processes in two Italian oncology centers - Daniela Bencardino; Fabiana Marchetti; Cristina Mazzi; Marianna Ferrari; Francesca Garibaldi; Giulia Ferrera; Giulia Ponti; Chiara Altavilla; Laura Rossi; Matteo Verzè; Vanda Salutari; Vincenzina Mora; et al. (Journal of Pharmaceutical Innovation, 2026)

Prenatal exposure to fine particulate matter PM2.5 and small for gestational age: a Bayesian model for area-based data in Milan - Simone Colombara; Rossella Murtas; Sara Tunesi; Alessandra Guglielmi; Antonio Giampiero Russo; Paola Angelini; Serena Broccoli; Marco Monti; Nicola Caranci; Katia Raffaelli; Daniela Fortuna; Paolo Giorgi Rossi; et al. (Environmental and Ecological Statistics, 2025)

Progress and challenges in obesity pharmacotherapy: semaglutide as a milestone - Francesco Ferrara; Denise Bazzani; Barbara Crivelli; Elisa Danieli; Pietro Gazzola; Greta Guarnieri; Giulia Handschin; Claudia Lauria; Carlotta Marchetti; Emanuele Sbraga; Carmen Zero; Andrea Zovi; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Association between long-term exposure to air pollution and cause-specific mortality within five Italian longitudinal metropolitan studies - Federica Nobile; Nicola Caranci; Elena Strippoli; Valentina Adorno; Alessandra Allotta; Lucia Bisceglia; Ida Galise; Claudio Gariazzo; Sara Maio; Paola Michelozzi; Walter Pollina Addario; Andrea Ranzi; et al. (Atmospheric Environment, 2024)

Meltwater-driven sediment transport dynamics in two contrasting alpine proglacial streams - Michael Engel; Velio Coviello; Sara Savi; Anuschka Buter; Andrea Andreoli; Shusuke Miyata; Giulia Marchetti; Vittoria Scorpio; Sara Rathburn; Lindsey Nicholson; Francesco Comiti (Journal of Hydrology, 2024)

Advancing river monitoring using image-based techniques: challenges and opportunities - Salvatore Manfreda; Domenico Miglino; Khim Cathleen Saddi; Seifeddine Jomaa; Anette Eltner; Matthew Perks; Salvador Peña-Haro; Thom Bogaard; Tim H.M. van Emmerik; Stefano Mariani; Ian Maddock; Flavia Tauro; et al. (Hydrological Sciences Journal, 2024)

Air pollution and oxidative stress in adults suffering from airway diseases. Insights from the Gene Environment Interactions in Respiratory Diseases (GEIRD) multi-case control study - Giulia Squillacioti; Valeria Bellisario; Federica Ghelli; Alessandro Marcon; Pierpaolo Marchetti; Angelo G. Corsico; Pietro Pirina; Sara Maio; Massimo Stafoggia; Giuseppe Verlato; Roberto Bono (Science of The Total Environment, 2024)

Limitations in the use of Sentinel-1 data for morphological change detection in rivers - Giulia Marchetti; Andrea Manconi; Francesco Comiti (International Journal of Remote Sensing, 2023)

Relationship of long-term air pollution exposure with asthma and rhinitis in Italy: an innovative multipollutant approach - Sara Maio; Salvatore Fasola; Alessandro Marcon; Anna Angino; Sandra Baldacci; Maria Beatrice Bilò; Roberto Bono; Stefania La Grutta; Pierpaolo Marchetti; Giuseppe Sarno; Giulia Squillacioti; Ilaria Stanisci; et al. (Environmental Research, 2023)

Association between short-term exposure to air pollutants and cause-specific daily mortality in Italy. A nationwide analysis - Claudio Gariazzo; Matteo Renzi; Alessandro Marinaccio; Paola Michelozzi; Stefania Massari; Camillo Silibello; Giuseppe Carlino; Paolo Giorgi Rossi; Sara Maio; Giovanni Viegi; Massimo Stafoggia; Sandra Baldacci; et al. (Environmental Research, 2023)

Evaluation of three commercial assays for SARS-CoV-2 molecular detection in upper respiratory tract samples - Flora Marzia Liotti; Giulia Menchinelli; Simona Marchetti; Grazia Angela Morandotti; Maurizio Sanguinetti; Brunella Posteraro; Paola Cattani (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
The increasing COVID-19 widespread has created the necessity to assess the diagnostic accuracy of newly introduced (RT-PCR based) assays for SARS-CoV-2 RNA detection in respiratory tract samples. We compared the results of the Allplex™ 2019-nCoV assay with those of the Simplexa™ COVID-19 Direct assay and the Quanty COVID-19 assay, respectively, all performed on 125 nasal/oropharyngeal swab samples of patients with COVID-19 suspicion. Fifty-four samples were positive, and 71 were negative with the Allplex™ assay, whereas 47 of 54 samples were also positive with the Simplexa™ assay. The Quanty assay detected 55 positive samples, including the 54 positive samples with the Allplex™ assay and 1 sample that was Allplex™ negative but Simplexa™ positive. Using a consensus result criterion as the reference standard allowed to resolve the eight samples with discordant results (one Allplex™ negative and seven Simplexa™ negative) as truly false negative. Interestingly, a Spearman’s negative association was found between the viral RNA loads quantified by the Quanty assay and the C T values of RT PCRs performed with either the Allplex™ assay or the Simplexa™ assay. However, the strength of this association was higher for the Allplex™ assay (N gene, ρ = − 0.92; RdRP gene, ρ = − 0.91) than for the Simplexa™ assay (ORF1ab gene, ρ = − 0.65; S gene, ρ = − 0.80). The Allplex™ 2019-nCoV, the Simplexa™ COVID-19 Direct, and the Quanty COVID-19 assays yielded comparable results. However, the role these assays might play in future clinical practice warrants larger comparison studies.

Peripheral and cerebrospinal fluid immune activation and inflammation in chronically HIV-infected patients before and after virally suppressive combination antiretroviral therapy (cART) - E. Merlini; F. Iannuzzi; A. Calcagno; F. Bai; M. Trunfio; A. d’Arminio Monforte; S. Bonora; Giulia Marchetti (Journal of NeuroVirology, 2018)